PELATIHAN TOEFL PREPARATION PADA SISWA SMA N 1 STABAT - muhammad hassan; Rosmen Rosmen; Fernando de napoli Marpaung; Supriadi; Nurantika (Jurnal Pengabdian Kepada Masyarakat, 2023)
TOEFL is a test that is widely used in non-native English speaking countries to measure their English proficiency. The TOEFL certificate is very important for a number of purposes such as loan application requirements, registration for college both at home and abroad, applying for jobs, requirements for promotion, and so on. Given the urgency of being able to answer TOEFL questions, knowledge of TOEFL and tricks for doing it is necessary. Even so, doing the questions and getting a high score is not easy for everyone. At least that is what the students of SMA Negeri 1 Srabat described in personal interviews. Therefore, the solution offered is the provision of TOEFL PREPARATION training. From the TOEFL training activities which were carried out starting on January 28, 2023, it was found that there was a significant increase in students' TOEFL scores before and during an activity. In the future, it is hoped that the results of this dedication can broaden students' insight into tips and tricks for conquering the TOEFL so that they can achieve high scores which will eventually open up wider opportunities for them.